Rebel by vocation : Seán O'Faoláin and the generation of The Bell - Carson, Niall (Book collections on Project MUSE., 2017)
This is a comprehensive study of one of the most influential literary groups in post-independence Ireland: the writers and editors of the literary magazine The Bell. Seacutean O'Faolacuteain and the generation of writers that matured in the shadows of W. B. Yeats and James Joyce dominated the literary landscape in Ireland in the build-up to, and during, the Second World War. This is their story, as told through the history of one journal: The Bell. Working with previously unpublished archival material, this study looks to illuminate the relationships, disputes and loves of the contributors to Ireland's most important 'little magazine' under the guiding influence of its founding editor, Seacutean O'Faolacuteain. In doing so, it sheds new light on O'Faolacuteain's early influences and his attitude towards the Church and the state in Ireland.